Analisis Fungsi Pengawasan Pemerintah Daerah terhadap Pengelolaan Lingkungan di Sekitar Danau Lut Tawar, Kabupaten Aceh Tengah - Mukhsin; Cut Khairani; Siti Aisyah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Activities around Lake Lut Tawar have resulted in a decrease in the lake's Water Quality Index (WQI) over the past three years. The negative impacts of these activities affect the condition and status of Lake Lut Tawar, including a decline in endemic fish populations such as the Depik fish, siltation of the lake, and reduction in the lake area due to activities related to hotels, homestays, floating net cages, and reclamation or landfilling of the lake. This research aims to analyze the Local Government's Supervision Function in Environmental Management concerning businesses or activities around Lake Lut Tawar, Central Aceh Regency, and to identify the obstacles in implementing this function.The research method employed is qualitative, with assessment indicators including the Supervision Preparation Stage, the Supervision Implementation Stage, and the Post-Supervision Stage. According to the supervision theory proposed by Damopolii and Kurniawati, the results indicate that Environmental Compliance Supervision by the Central Aceh Regency Environmental Service is considered poor. This is evident from the preparatory stage through to the post-supervision stage conducted by the Central Aceh District Environmental Service. The data used in this study includes both primary and secondary sources, collected through interviews, observations, and documentation. The study found that the Local Government Supervision Function in the Environmental Sector carried out by the Central Aceh District Environmental Service has not been operating optimally. The obstacles in performing the duties and authority of environmental supervision and monitoring at the Central Aceh District Environmental Service are categorized into internal and external obstacles. The study recommends that the Regional Government of Central Aceh Regency develop a Detailed Spatial Plan (RDTR) for Lake Lut Tawar to serve as a guide for business actors and the community in conducting environmental management.